Nutritional care practices for children from 6 to 24 months old by Cham ethnic mothers - Tran, Quang Hien (International Journal of Contemporary Pediatrics, 2024)
Background: This study aims to explore the nutritional care practices for children from 6 to 24 months old by Cham ethnic mothers in Tan Chau town, An Giang province in 2018. Methods: A cross-sectional study was conducted on Cham ethnic children aged from 6 to 24 months and their mothers living in Tan Chau town, An Giang province. Results: The rate of mothers practicing proper and sufficient prenatal care during pregnancy is 74.4%; the rate of mothers engaging in lighter work than before pregnancy is 64.2%; the rate of mothers eating more than before pregnancy is 72.2%; the rate of mothers taking iron supplements during pregnancy is high at 85%. Practices regarding the timing of weaning children are not good, with 36.8% of mothers weaning children at the wrong time. Practices for feeding children supplementary foods are relatively good: 90.7% of mothers feed their children at the right time, however, the rate of mothers providing children with a complete range of food groups is only 23.0%. Maternal care practices for sick children have many shortcomings, with 81.7% of mothers feeding children incorrectly when they have diarrhea, and only 38.4% of children receiving oral rehydration solution (ORS) when they have diarrhea. Personal hygiene practices of the mother and child care are not good, with 24.3% of mothers not properly performing hand hygiene for themselves and their children. Conclusions: We need to strengthen propaganda and consulting work for each group of subjects, especially the Cham ethnic people, on nutritional care practices for children from 6-24 months old.